THE DEVELOPMENT OF LEARNING DESIGN USING ASSURE MODELS AT ELEMENTARY SCHOOLS - Stavinibelia, Stavinibelia; Aris, Affandy Agusman; Kholik, Nur; Efendi, Nofriza; Sari, Ika Purnama; Saman, Saman; Oktira, Yona Syaida (Dharmas Education Journal (DE_Journal), 2023)
Meaningful and enjoyable learning will lead students to memorable learning experiences, one of which can be achieved through learning activities that emphasize the involvement of student learning activities. The purpose of this research is to describe the validity, practicality, and effectiveness of the results of learning design with the ASSURE model in elementary schools. This research is research development (research and development). The model used as the basis for developing this learning design is ASSURE. The procedure for developing this learning design is in accordance with the stages of the ASSURE development model. The test subjects in this study were fourth grade students at SDN 16 Sitiung in the odd semester of the 2022/2023 academic year. The results of this study show validity at 90% in the very valid category. The practicality of the results of the ASSURE model learning design model with a percentage of 93%. While the effectiveness of the implementation of lesson plans, activities and learning outcomes of students with a percentage of 90%. Based on the results of the study it was concluded that the learning design with the ASSURE model developed was valid, practical and effective.